Geographic Difference Shaped Human Ocular Surface Metagenome of Young Han Chinese From Beijing, Wenzhou, and Guangzhou Cities - Deng, Yuhua; Wen, Xiaofeng; Hu, Xiao; Zou, Yanli; Zhao, Chan; Chen, Xuejiao; Miao, Li; Li, Xifang; Deng, Xiuli; Bible, Paul W.; Ke, Hongmin; Situ, Jiahao; et al. (Investigative ophthalmology & visual science, 2020)
Microbial ecosystems interact with the human body and affect human health. The microbial community on the ocular surface remains an underexplored territory despite its importance as the first line of defense barrier that protects the eye and ultimately sight. We investigated how age and sex affected human ocular surface microbiome, and in the present study wanted to understand how geographic difference shaped the microbiome in the ocular surface. We collected conjunctival specimens of 172 eyes from 86 healthy volunteers living in three Chinese cities, namely, Guangzhou, Wenzhou, and Beijing. Using the direct metagenomic shotgun sequencing approach, we characterized how geographic difference affected the human ocular microbiome. We surveyed the taxonomic composition and metabolic function of the microbiota on human ocular surface. We showed that the ocular surface microbiota was composed of bacteria, viruses, and fungi. A geographical difference in both composition and function of the conjunctival microbiome suggests that the environment people lived in shapes their conjunctival microbiome, especially the dominate species. Our study provides a reference catalog of the healthy conjunctival metagenome and raises a concern for environmental influences on the ocular surface microbiome.